Forced Migrant Counter Cultural (Co)Productions - Mbasalaki, Phoebe Kisubi (2024)
This article investigates the dynamics of knowledge co‐creation through the lens of documentary filmmaking with forced migrants in South Africa. Drawing on empirical research done in South Africa in 2022, both narration and the documentary film became potent modes of knowledge co‐production, illuminating how cultural productions contribute to shaping our understanding of forced migration and its associated challenges. Emphasising the prevalence of anti‐migrant rhetoric in South Africa and the prevalence of violence meted out against (forced) African migrant workers, this article identifies parallels with global discourses surrounding migrancy, where false nationalisms vilify migrants as scapegoats for societal issues. Central to the overarching claim of the article is the integration of border theory as an epistemological framework. We centralise the “bodily border” as the ultimate marker of differentiation where violence is enacted through the frameworks of “recognising strangers” and can be as severe as death. We unpack the makings and framework of the nationalist discourse in South Africa that targets (forced) African migrants—one rooted in citizenship without content, lacerated Pan‐Africanism through colonial borders, and bodily borders, among others. We then examine the documentary film as a cultural text, a structured narrative that blends factual storytelling with artistic representation, highlighting its role in co‐producing migrant knowledges. Therefore, the documentary film functions not only as a visual and narrative counterpoint to dominant anti‐immigration discourse but also as a co‐constructed medium for exploring and articulating the complex notions of home experienced by African (forced) migrants in South Africa. Consequently, the article argues that integrating border theory into the process of knowledge co‐creation not only deepens our understanding of forced migration but also acts as a catalyst for reshaping societal narratives, fostering a more cohesive and integrated vision of Africa.